The shariah and law : An analysis - Muhammed, Muneer Kuttiyani; Ali, Mohd Mumtaz (Global Academic Excellence, 2017)
Although the scholarly discussions on Shariah has significantly been increased recently, many of these deliberations leave a distorted image of the Shariah. This paper attempts to explore scope and role of the Shariah by analyzing its etymology and historical conceptions in the light of the Qur’anic statements [5:48, 45:18 and 5:48]. It will also investigate the various intellectual reflections of scholars and exegesis. Contrary to the general perception of the Shariah merely as ‘Islamic law, this paper makes a comparative analysis between the Shariah and law by highlighting the distinctive features of the Shariah. As a part of this analysis, some major higher universal principles of the Shariah which seem more significant to the multi-religious society will also be discussed in this paper. An approach of combining the conceptual and comparative analysis along with philosophical reflections and inter-textual reading of the various scholars have been employed in this research. The study presents the Shariah as a significant alternative dynamic system of life which seem more relevant in the multi-religious and multi-cultural societies.